Clinical Characteristics of the Patients with COVID-19 Death in a Tertiary Care Hospital (The Planet, 2024)
Introduction: Corona virus disease-2019 (COVID-19) has killed millions of people around the globe. Several thousands of people have died of the disease in Bangladesh. This highly contagious disease is continuing to infect the people of the world.  Methods and Materials: To review the demographic and clinical features of patients who died of COVID-19 at Bangabandhu Sheikh Mujib Medical College Hospital, Faridpur, Bangladesh during 2021-2022. This retrospective observational study evaluated the demographic features and clinical characteristics of 69 patients with COVID death. Patients of 18 years or more with COVID-19, confirmed by positive Reverse Transcriptase (RT-PCR) reports of nasopharyngeal swabs who died during hospital stay were enrolled in this study. Various demographic and clinical features of the patients were analyzed using Statistical Package for Social Sciences version 29. Results: The mean age of the respondents was 63.45 (±13.80) years. Of 69 patients, 50 (72.5%) were male and 19 (27.5%) were female. Of the respondents, 36 (52.2%) patients had high socioeconomic status. According to occupation, the most patients were businessmen (25, 36.2%), followed by housewives (16, 23.2%) and service holders (13, 18.8%). Common comorbidities were diabetes (38, 55.1%), hypertension (35, 50.7%), smoking (17, 24.6%), ischemic heart disease (15, 22.1%) and stroke (7, 10.1%). Commonly observed symptoms were breathlessness, fever, cough, fatigue, anorexia, loss of taste and loss of smell. Among the patients, 60 (87.0%) had severe and 9 (13.0%) had critical disease. Conclusion: Higher age group, male sex, higher socioeconomic status, sedentary lifestyle, and different comorbidities, such as diabetes, hypertension, smoking, ischemic heart disease and stroke were more frequently observed in the patients with COVID-19 death.
Keywords: COVID-19; Critical; Death; Severe